2006
DOI: 10.1038/nature04970
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal ensemble control of prosthetic devices by a human with tetraplegia

Abstract: Neuromotor prostheses (NMPs) aim to replace or restore lost motor functions in paralysed humans by routeing movement-related signals from the brain, around damaged parts of the nervous system, to external effectors. To translate preclinical results from intact animals to a clinically useful NMP, movement signals must persist in cortex after spinal cord injury and be engaged by movement intent when sensory inputs and limb movement are long absent. Furthermore, NMPs would require that intention-driven neuronal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

35
2,209
0
26

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 2,883 publications
(2,270 citation statements)
references
References 40 publications
35
2,209
0
26
Order By: Relevance
“…Whenever the user induces a voluntary modification of these patterns, the BCI system is able to detect it and to translate it into an action that reflects the user's intent. Several animal and some human studies have shown the possibility to use electrical brain activity recorded within the brain to directly control the movement of robots or prosthetic devices in real time using microelectrodes implanted within the brain [6] [7][8] [9] [10]. Other BCI systems depend on brain activity recorded non-invasively from the surface of the scalp using electroencephalography (EEG).…”
Section: Introductionmentioning
confidence: 99%
“…Whenever the user induces a voluntary modification of these patterns, the BCI system is able to detect it and to translate it into an action that reflects the user's intent. Several animal and some human studies have shown the possibility to use electrical brain activity recorded within the brain to directly control the movement of robots or prosthetic devices in real time using microelectrodes implanted within the brain [6] [7][8] [9] [10]. Other BCI systems depend on brain activity recorded non-invasively from the surface of the scalp using electroencephalography (EEG).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic implant surgery once the rats reached the acquisition criterion, chronic implant surgery was performed [30,31] . Briefly, the rat was anesthetized with chloral …”
mentioning
confidence: 99%
“…Using the signals obtained from this electrode array, a BCI system enabled the patient to open simulated e-mail, operate a television, open and close a prosthetic hand, and perform rudimentary actions with a robotic arm. 11 In 2011, Krusienski and Shih 12 demonstrated that signals recorded directly from the cortical surface (electrocorticography [ECoG]) can be translated by a BCI to allow a person to accurately spell words on a computer screen. Brain-computer interface research is growing at an extremely rapid rate, as evidenced by the number of peer-reviewed publications in this field over the past 10 years (Figure 1).…”
Section: Milestones In Bci Developmentmentioning
confidence: 99%